Perspectives on content and delivery of the ABLE 1.0 intervention programme - Kristina Tomra Nielsen; Marie Bangsgaard Bang; Marc Sampedro Pilegaard; Vita Hagelskjær; Eva Ejlersen Wæhrens (Scandinavian Journal of Occupational Therapy)
Background The occupational therapy intervention programme ABLE 1.0 was designed to enhance the ability to perform activities of daily living in persons living with chronic conditions. There is a need to determine if content and delivery of the ABLE 1.0 are acceptable among occupational therapists (OTs) and clients after having delivered or received the programme, respectively.Objectives The paper reports on evaluation of content and delivery of the ABLE 1.0 among OTs and clients. This, in terms of acceptability of intervention in principle, and perceived value, benefits, harms, or unintended consequences of the intervention.Material and methods Qualitative semi-structured interviews were conducted with OTs having delivered and clients having received ABLE 1.0 in a Danish municipality. Content analysis was performed.Findings Two OTs and three clients participated. Analyses revealed six categories related to content and delivery; ‘Overall perception of the programme’; ‘Potential for implementation’; ‘Evaluation, goal setting and clarification of reasons for ADL task performance problems’; ‘Intervention: compensatory solutions’; ‘Format and duration’ and ‘Preconditions for delivery’.Conclusions and significance The findings provided valuable information used for further development of the ABLE programme.